2019
DOI: 10.1002/asjc.2065
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time optimal energy management for a fuel cell/battery hybrid system

Abstract: An energy management strategy is proposed for a class of fuel cell∕battery hybrid systems. In such hybrid systems, a fuel cell system is the main power source, and a lithium-ion battery is the auxiliary power source. In order to manage the system power at the next moment in a reasonable way, a load current filter with bounded estimation errors is designed to estimate the load current.Then, a real-time optimal energy management algorithm is proposed to optimize economy consumption of the hybrid system. By takin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The most important feature of the real-time optimization strategies is the processing power of the information gathered from the ESS for the purpose of energy control automa-tion to prevent the aging of the components. Even though the design of such algorithms is more difficult to achieve, compared to the other energy management strategies, real-time strategies are important because the realization of FCEVs must have a competitive finish on the world market [116,131].…”
Section: Real-time Optimization Strategymentioning
confidence: 99%
“…The most important feature of the real-time optimization strategies is the processing power of the information gathered from the ESS for the purpose of energy control automa-tion to prevent the aging of the components. Even though the design of such algorithms is more difficult to achieve, compared to the other energy management strategies, real-time strategies are important because the realization of FCEVs must have a competitive finish on the world market [116,131].…”
Section: Real-time Optimization Strategymentioning
confidence: 99%
“…In this paper, the optimization problem (28) is solved by the active‐set method [37]. In fact, other optimization algorithms, for example, fast gradient method and interior point method, can also solve such optimization problem [38].…”
Section: Contouring Controller Designmentioning
confidence: 99%
“…Moreover, the additional degrees of freedom in the MESs make the centralized algorithms substantially complicated and time-consuming to be solved. In this respect, some papers have focused on the distributed optimization algorithms to solve the PAS optimization problems [30][31][32][33][34]. In [30], a projected interior point method is proposed under the framework of model predictive control (MPC) to solve the power allocation problem and concluded that this strategy is faster than CVX tool, which is a general-purpose convex optimization software.…”
Section: Introductionmentioning
confidence: 99%
“…In [31], CVX tool is utilized to solve a formulated convex optimization problem for a plug-in FCV, and it is shown that the proposed approach can effectively distribute the power between the power sources and also find the optimal sizes of each source. In [32], the slew rate of the PEMFC current and the battery state of charge (SoC) are considered to formulate the PAS in the form of quadratic programming (QP). Subsequently, a solver is utilized to solve the QP problem based on the alternating direction method of multipliers (ADMM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation